Teaching French for Specific Purposes - Atamirzayeva, Ezoza (Indonesian Journal Publisher, 2024)
Since 2009 a new didactic concept of teaching foreign language named “French for university purposes” is being developed. This article describes the stages of its development and methods of teaching French to foreign students using approaches based on the analysis of their academic goals and professional needs. To develop this new concept efficiently, teachers should be actively involved in theoretical and practical research in this field by taking advantage of the expertise contained in the “English for Academic Purposes” that has been in development for the last 20 years